Um estudo do movimento teórico de Ferdinand de Saussure no manuscrito Phonétique - Lima, Thayanne Raísa Silva e (2019)
This work seeks to investigate Ferdinand de Saussure’s theoretical movement regarding the phonic aspect of the language (FAL – in Portuguese, AFL), especially in his manuscript entitled Phonétique (1881-1884). The investigation was carried out by dividing the thesis into three distinct moments. In the first one, we established the pre-Saussurean studies that take into account the AFL both the earliest and most representative teachings, and the precepts of nineteenth-century linguists; in the first part of this chapter, we chose to reflect on Plato's Cratylus and the Essay On The Origin Of Languages written by Rousseau. For the second part of the chapter, the nineteenth century, we chose to address some of the most active scholars in AFL’s research, namely Jacob Grimm (1785-1863), August Schleicher (1821-1868) and Hermann Paul (1846-1921), representatives of Comparative Grammar and the Neogrammarian School. In the second moment, we examined the Saussurean research on the AFL in Phonétique and some specific works that addressed the theme, such as: those before this manuscript, the Essai (1874) and the Mémoire (1878), and those more than twenty years later of it, the courses of General Linguistics, from the point of view of the students' notebooks and the posthumous work of Saussure, the Course in General Linguistics. In the third and last moment, we established these two periods and their discussions in relation to Phonétique, and situate our research on the Saussurean theoretical movement in the light of Silveira's studies. Based on the author's precepts, we sought to reflect on this movement by emphasizing the points of tension present in the manuscript text in comparison with both the pre-Saussurean moment and the time of Saussure's classes in Geneva. In this sense, we started with a reflection that puts the linguist at the same time approaching and distancing himself from the notions established by the linguists of the nineteenth century. In addition, it was possible to note that in distancing himself from the studies developed in that century, Saussure establisheed a connection with one of his most striking research goals: his theorizing about language. Based on AFL's Saussurean research, more than two decades before the General Linguistics courses at the University of Geneva, the linguist showed a theoretical movement capable of establishing a shift from the studies of his time, fundamentally empirical, to theorizing. Furthermore, it was possible to observe that as a consequence of this theoretical shifting, there were in 1881-84 precepts that led the linguist to come across definitions, distinctions of terms and concepts responsible for taking him to the notion of the subject of Linguistics. Thus, the Phonétique, written years before the courses of General Linguistics, indicates Saussure’s theoretical movement that does not strain of being repeated in his works, in other words, his search for the Linguistics’ subject: the language.